2015
DOI: 10.1152/ajpregu.00515.2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term measurement of renal cortical and medullary tissue oxygenation and perfusion in unanesthetized sheep

Abstract: Calzavacca P, Evans RG, Bailey M, Lankadeva YR, Bellomo R, May CN. Long-term measurement of renal cortical and medullary tissue oxygenation and perfusion in unanesthetized sheep. Am J Physiol Regul Integr Comp Physiol 308: R832-R839, 2015. First published March 11, 2015 doi:10.1152/ajpregu.00515.2014.-The role of renal cortical and medullary hypoxia in the development of acute kidney injury is controversial, partly due to a lack of techniques for the long-term measurement of intrarenal oxygenation and perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 46 publications
1
67
0
Order By: Relevance
“…The probes are precalibrated by the manufacturer. We have recently shown that the values of LDF and tPO2 generated by these probes in the cortex and medulla of awake sheep are stable over many days and respond rapidly and reproducibly to changes in renal perfusion pressure (3). Provided the probes are not damaged during the experiment, values of PO2 obtained in saline solution saturated with CO2 (ϳ0 mmHg) or room air (ϳ160 mmHg) are similar before and after implantation.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations
“…The probes are precalibrated by the manufacturer. We have recently shown that the values of LDF and tPO2 generated by these probes in the cortex and medulla of awake sheep are stable over many days and respond rapidly and reproducibly to changes in renal perfusion pressure (3). Provided the probes are not damaged during the experiment, values of PO2 obtained in saline solution saturated with CO2 (ϳ0 mmHg) or room air (ϳ160 mmHg) are similar before and after implantation.…”
Section: Methodsmentioning
confidence: 93%
“…At the same operation, two custom-built fiber-optic probes (CP-004-001; Oxford Optronix, Oxford, UK), with 20 mm of optical fiber extending from the outer sheath, were inserted in the kidney, as previously described (3). In brief, the outer sheath of the probes was glued to a plastic sheet, which was secured to the kidney capsule with cyanoacrylate adhesive.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This corroborates the hypothesis that oxygen delivery is the most important determinant of this circadian pattern in oxygenation. Recently, 24-h oxygen recordings in the kidneys have been obtained in sheep (Calzavacca et al, 2015). In that study, a clear 24-h pattern in tissue oxygenation of the kidneys was absent.…”
Section: Discussionmentioning
confidence: 99%